Childhood Trauma and Sleep Among Young Adults With a History of Depression: A Daily Diary Study - Hamilton, Jessica L.; Brindle, Ryan C.; Alloy, Lauren B.; Liu, Richard T. (Frontiers in Psychiatry, 2018)
Child maltreatment and sleep disturbances are particularly prevalent among individuals with a history of depression. However, the precise relation between child maltreatment and sleep within this population is unclear. The present study evaluated childhood maltreatment and trauma as a predictor of sleep duration and insomnia symptoms among young adults with prior depression. A total of 102 young adults (18-22; 78% female) with a history of clinical or subclinical depression completed an in-person visit with diagnostic interviews and questionnaires of childhood trauma (maltreatment and general trauma), and two weeks of daily assessments of sleep and depressive symptoms using internet-capable devices. Using multilevel modeling, we found that only childhood emotional neglect significantly predicted higher levels of insomnia symptoms over the two weeks, controlling for daily depression. Neither childhood maltreatment nor trauma predicted sleep duration. Our findings highlight a unique relationship between emotional neglect and insomnia symptoms among individuals with a depression history that, given prior research, may potentially play a role in depression recurrence and represent a potential treatment target.